Preparation method of negative pole piece for lithium ion battery and lithium ion battery

By forming a porous structure during the preparation of the negative electrode sheet of the lithium-ion battery, the powdering and polarization problems caused by volume expansion during the charging and discharging of the negative electrode sheet is solved, and the cycle performance and rate performance of the battery are improved.

CN119695084AActive Publication Date: 2025-03-25SHENZHEN HIGHPOWER TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411998894.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The negative electrode sheet of lithium-ion battery has volume expansion problems during charging and discharging, which leads to the powdering and falling off of the electrode material, affecting the cycle life and stability of the battery. At the same time, the increase in the electrode thickness leads to a decrease in the lithium ion transmission efficiency, which easily leads to polarization.

Method used

By forming a porous structure on the surface of the pole sheet during the preparation of the negative electrode sheet, NH4HCO3 is used to decompose the generated gas in the drying step, which promotes the formation of the pole structure, reduces the tortuosity, improves the lithium ion conduction rate, and reduces the concentration polarization of the pole sheet.

Benefits of technology

It has achieved the reduction of tortuosity of the negative electrode sheet, shortening the migration distance of lithium ions, improving the conduction rate of lithium ions in the negative electrode sheet, delaying the aging of the negative electrode sheet of the battery, and improving the rate performance and cycling performance of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695084A_ABST
    Figure CN119695084A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a negative pole piece for a lithium ion battery and the lithium ion battery. The preparation method comprises the following steps: mixing a CMC-Li binder and a PAA binder to obtain a negative electrode glue solution; uniformly mixing the negative electrode glue solution with a negative electrode active material, a conductive agent, NMP, NH4HCO3 and deionized water, and then adding an SBR binder to prepare negative electrode slurry with the discharging viscosity of 6500-9500 Pa.s; and coating the surface of a negative electrode current collector with the negative electrode slurry, drying and rolling to obtain the negative electrode plate. According to the scheme provided by the invention, the porous structure can be formed in the pole piece in the preparation process of the negative pole piece, the porous negative pole piece with high thickness is prepared, the tortuosity of the thick negative pole piece is reduced, the transmission rate of lithium ions in the negative pole piece is improved, the concentration polarization of the pole piece is reduced, and the rate capability and the cycle performance of a battery cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium ion battery preparation, and in particular to a method for preparing a negative electrode sheet for a lithium ion battery and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are the main force in the modern energy storage field, and energy density is one of the core indicators to measure the performance of batteries, which is directly related to the application potential of batteries in many fields.

[0003] As a new type of negative electrode material for lithium-ion batteries, silicon-carbon material has significant advantages. Silicon has a very high theoretical specific capacity of about 4200mAh / g, which is much higher than the 372mAh / g of graphite. This enables the silicon-carbon negative electrode to significantly increase the energy density of the battery, providing strong support for extending the service life of the equipment and improving the range of electric vehicles. However, silicon materials have serious volume expansion problems during the charging and discharging process, which can reach 300%-400%. Such drastic volume changes can easily lead to powdering and shedding of electrode materials, thereby affecting the cycle life and stability of the battery.

[0004] The use of silicon-carbon materials in the preparation of thick negative electrode sheets can accommodate more active substances and significantly improve the energy density of the battery. However, as the thickness of the electrode increases, the transmission distance of lithium ions inside the electrode becomes longer, resulting in reduced ion transmission efficiency, which is prone to cause polarization and affects the battery's charge and discharge performance and cycle life. Summary of the invention

[0005] In order to solve or partially solve the problems existing in the related art, the present application provides a method for preparing a negative electrode sheet for a lithium ion battery and a lithium ion battery, which can form a porous structure on the surface of the electrode sheet during the preparation process of the negative electrode sheet to make a porous thick electrode negative electrode sheet, reduce the tortuosity of the thick electrode negative electrode sheet, increase the conduction rate of lithium ions in the negative electrode sheet, reduce the concentration polarization of the electrode sheet, and improve the rate performance and cycle performance of the battery cell.

[0006] The first aspect of the present application provides a method for preparing a negative electrode sheet for a lithium ion battery, comprising the following steps: 1) Mixing CMC-Li binder and PAA binder to obtain negative electrode glue; 2) The negative electrode glue is mixed with the negative electrode active material, conductive agent, NMP, NH 4 HCO 3 After being evenly mixed with deionized water, an SBR binder is added to prepare a negative electrode slurry with a discharge viscosity of 6500~9500Pa·s; 3) coating the negative electrode slurry on the surface of the negative electrode current collector, drying and rolling to obtain a negative electrode sheet; the NH 4 HCO3 During the drying step, decomposition generates gas, which promotes the formation of a porous structure in the negative electrode sheet.

[0007] In some embodiments of the present application, the step 2) includes: 2a) taking a portion of the negative electrode glue in step 1) as a primary mixed negative electrode glue, mixing the primary mixed negative electrode glue with the negative electrode active material, the conductive agent and deionized water, and stirring for 90 to 120 minutes at a speed of 100 to 300 rpm to obtain a primary conductive glue; 2b) taking a portion of the negative electrode glue in step 1) as a secondary mixed negative electrode glue, adding the secondary mixed negative electrode glue to the primary conductive glue, stirring for 60 to 80 minutes at a speed of 1800 to 2000 rpm to obtain a secondary conductive glue; 2c) taking a portion of the negative electrode glue in step 1) as a tertiary mixed negative electrode glue, adding the tertiary mixed negative electrode glue, deionized water, NMP and NH 4 HCO 3 , stirring for 60-90 minutes at a rotation speed of 1800-2100 rpm; after mixing evenly, adding SBR binder to prepare a negative electrode slurry with a discharge viscosity of 6500-9500 Pa·s.

[0008] In some embodiments of the present application, the volume ratio of the primary mixed negative electrode paste, the secondary mixed negative electrode paste and the tertiary mixed negative electrode paste is (1.5~2.5):1:(1.5~2.5).

[0009] In some embodiments of the present application, the total amount of the binder is 2.5-3.5wt% of the sum of the mass of the negative electrode glue, the negative electrode active material, and the conductive agent; The NH 4 HCO 3 The amount used is 0.6-1.2wt% of the sum of the mass of the negative electrode glue, the negative electrode active material and the conductive agent.

[0010] In some embodiments of the present application, the total amount of the binder is 4 HCO 3 The dosage ratio is (2.5~4):1.

[0011] In some embodiments of the present application, the negative electrode active material is selected from a composite material of graphite and silicon carbon, and the mass ratio of the graphite to silicon carbon is (90~94):(3~7).

[0012] In some embodiments of the present application, the conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers, and superconducting carbon.

[0013] In some embodiments of the present application, the negative electrode current collector is selected from copper foil with a conductive carbon black primer, and the thickness of the conductive carbon black primer is 0.5-1 μm.

[0014] In some embodiments of the present application, in the step 1), a CMC-Li binder with a solid content of 1 to 1.5 wt% and a PAA binder with a solid content of 3 to 8 wt% are mixed to obtain a negative electrode glue, and the mass ratio of the CMC-Li binder to the PAA binder is 1: (2 to 5).

[0015] In some embodiments of the present application, the drying temperature in step 3) is 95-110°C.

[0016] In some embodiments of the present application, the thickness of the negative electrode active material layer on the negative electrode plate is 50-70 μm.

[0017] A second aspect of the present application provides a negative electrode plate, which is prepared by the above-mentioned preparation method.

[0018] A third aspect of the present application provides a lithium-ion battery, comprising a negative electrode sheet prepared by the above preparation method.

[0019] A fourth aspect of the present application provides an electrical device or various energy storage systems using batteries as energy storage elements, which include the above-mentioned lithium-ion battery.

[0020] The technical solution provided by this application may have the following beneficial effects: By introducing a non-polluting pore-forming agent NH40 in the preparation process of the negative electrode sheet without introducing other magnetic impurities, 4 HCO 3 , which is thermally decomposed to form CO during the electrode drying process 2 , H 2 O、NH 3 The lithium ions are discharged, thereby forming a porous structure in the electrode sheet, and a porous thick electrode negative electrode sheet is formed after rolling, which reduces the tortuosity of the negative electrode sheet, shortens the migration distance of lithium ions, improves the conduction rate of lithium ions in the negative electrode sheet, reduces the concentration polarization of the electrode sheet, and improves the rate performance and cycle performance of the thick electrode battery cell.

[0021] The technical solution of the present application also includes: by strictly controlling the mixing order between the glue and the negative electrode active material and the conductive agent and other materials during the preparation of the negative electrode plate, it is beneficial for the glue to better wet the main material, increase the bonding force between the particles of the negative electrode active material, the conductive agent and the like, and between the particles and the negative electrode collector, help to slow down the pulverization of the negative electrode particles introduced by the silicon-carbon negative electrode due to repeated volume contraction and expansion, and the peeling between the negative electrode particles and the negative electrode collector, delay the aging of the negative electrode plate of the lithium-ion battery, and extend the service life of the battery cell.

[0022] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The above and other objects, features and advantages of the present application will become more apparent by describing in more detail the exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.

[0024] Figure 1 It is a schematic diagram of the process of preparing the negative electrode plate in Example 1 of the present application. DETAILED DESCRIPTION

[0025] To make the present invention easy to understand, the present invention will be described in detail below. However, before describing the present invention in detail, it should be understood that the present invention is not limited to the specific embodiments described. It should also be understood that the terms used herein are only for describing specific embodiments and are not intended to be limiting.

[0026] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0027] Where a numerical range is provided, it is to be understood that each intermediate value between the upper and lower limits of the range and any other provisions or intermediate values ​​in the specified range is encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included in the smaller ranges and are also encompassed within the present invention, subject to any explicitly excluded limits in the specified range. Where a specified range includes one or two limits, the scope excluding any or both of those included limits is also encompassed within the present invention. In the description of the present application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically limited.

[0028] Unless otherwise defined, all terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials or equivalent methods and materials described herein can also be used in the practice or testing of the present invention, preferred methods and materials are now described.

[0029] The use of silicon-carbon materials in the preparation of thick negative electrode sheets can accommodate more active substances and significantly improve the energy density of the battery. However, as the thickness of the electrode increases, the transmission distance of lithium ions inside the electrode becomes longer, resulting in reduced ion transmission efficiency, which is prone to cause polarization and affects the battery's charge and discharge performance and cycle life.

[0030] In view of the above problems, the embodiments of the present application provide a method for preparing a negative electrode sheet for a lithium ion battery, a negative electrode sheet and a lithium ion battery, which can form a porous structure on the surface of the sheet during the preparation of the negative electrode sheet to make a porous thick electrode negative electrode sheet, reduce the tortuosity of the thick electrode, increase the transfer rate of lithium ions in the negative electrode sheet, reduce the concentration polarization of the sheet, and improve the rate performance and cycle performance of the battery cell. The method for preparing a negative electrode sheet for a lithium-ion battery according to an embodiment of the present application comprises the following steps: 1) Mixing CMC-Li binder and PAA binder to obtain negative electrode glue; 2) Mix the negative electrode glue with the negative electrode active material, conductive agent, NMP, NH 4 HCO 3 After being evenly mixed with deionized water, an SBR binder is added to prepare a negative electrode slurry with a discharge viscosity of 6500~9500Pa·s; 3) Coat the negative electrode slurry on the surface of the negative electrode current collector, dry and roll to obtain the negative electrode sheet; NH 4 HCO 3 Decomposition during the drying step produces gas, which promotes the formation of a porous structure in the negative electrode sheet.

[0031] In the embodiment of the present application, a non-magnetic impurity, non-polluting pore-forming agent NH is introduced into the negative electrode slurry. 4 HCO 3 , which is thermally decomposed to form CO during the electrode drying process. 2 , H 2 O、NH 3The pore-forming agent ammonium bicarbonate has a low thermal decomposition temperature and can be decomposed into CO at 60°C. 2 , H 2 O、NH 3 In the preparation process of thick electrodes, no additional heating process is required. The coated electrode can be completely decomposed during the baking process, and no other impurity ions are introduced, which will not affect the performance of the battery cell. The preparation method is simple, easy to operate, and low in cost, which is conducive to application in industrial production.

[0032] Moreover, the negative electrode sheet preparation process is simple and easy to operate, the introduced pore-forming agent has low cost, is suitable for large-scale production, and has extremely high industrial production application value.

[0033] In some embodiments, the discharge viscosity of the negative electrode slurry is preferably 8000~9500Pa·s, and more preferably 8500~9000Pa·s. Optimizing the discharge viscosity of the negative electrode slurry can make the negative electrode slurry spread evenly on the surface of the negative electrode current collector during the subsequent coating process, ensure that the negative electrode active material and the conductive agent are evenly distributed on the surface of the current collector, ensure that the insertion and extraction process of lithium ions is smooth and uniform, and improve the battery capacity and cycle life. At the same time, the binder can be evenly distributed, improve the bonding force between the negative electrode particles such as the negative electrode active material and the conductive agent, and between the negative electrode particles and the surface of the negative electrode current collector, so that the negative electrode particles are firmly attached to the surface of the current collector, avoid the increase of the internal resistance of the battery caused by the shedding of the powder, and improve the cycle performance of the battery.

[0034] Furthermore, optimizing the discharge viscosity of the negative electrode slurry can make the pore former evenly dispersed in the slurry, ensure that the pore former is evenly present in the negative electrode active material layer, and avoid the pore former from precipitating or aggregating in the slurry. After drying, the pore former decomposes under the action of heat to form evenly distributed pores on the surface of the pole piece, and the pores can form regular structures, providing channels for the storage of electrolyte and the transmission of lithium ions, and improving the ionic conductivity and rate performance of the battery. If the viscosity is too low, the pore former may precipitate or aggregate in the slurry, and the distribution is uneven, and the negative electrode active material layer is easy to collapse, and pores cannot be effectively formed, or the formed pores are too small to meet the requirements of electrolyte and lithium ion transmission. If the viscosity is too high, it will hinder the drying and compaction process of the pole piece, and the pore former cannot be evenly dispersed, and uneven distribution will also occur, and the formed pore structure will be irregular, resulting in uneven distribution of local electrolyte, affecting the embedding and de-embedding process of lithium ions in the electrode, and reducing the charge and discharge efficiency and cycle life of the battery.

[0035] In some implementations, the above step 2) may specifically include: 2a) taking a portion of the negative electrode glue in step 1) as a primary mixed negative electrode glue, mixing the primary mixed negative electrode glue with the negative electrode active material, the conductive agent and deionized water, and stirring for 90 to 120 minutes at a speed of 100 to 300 rpm to obtain a primary conductive glue; 2b) taking a portion of the negative electrode glue in step 1) as a secondary mixed negative electrode glue, adding the secondary mixed negative electrode glue to the primary conductive glue, stirring for 60-80 minutes at a speed of 1800-2000 rpm to obtain a secondary conductive glue; 2c) Take a portion of the negative electrode glue in step 1) as the tertiary mixed negative electrode glue, add the tertiary mixed negative electrode glue, deionized water, NMP and NH 4 HCO 3 , stirring for 60-90 minutes at a rotation speed of 1800-2100 rpm; after mixing evenly, adding SBR binder to prepare a negative electrode slurry with a discharge viscosity of 6500-9500 Pa·s.

[0036] In the embodiment of the present application, in step 1), PAA and CMC-Li are mixed and stirred to form a negative electrode glue. CMC-Li is used as a dispersant for PAA, which is beneficial for PAA to be better dispersed in the dispersant. Then, the glue is mixed with the main material in batches (i.e., a primary mixed negative electrode glue, a secondary mixed negative electrode glue, and a tertiary mixed negative electrode glue), which is beneficial for the glue to better wet the main material, reduce the surface tension of the PAA binder, increase the bonding force between negative electrode particles and between negative electrode particles and current collectors, and help to slow down the pulverization of negative electrode particles and the peeling off from the current collector caused by repeated volume shrinkage and expansion of the silicon-carbon negative electrode, thereby delaying the aging of the negative electrode sheet of the battery and extending the service life of the battery cell.

[0037] Further, in step 1), a CMC-Li binder having a solid content of 1 to 1.5 wt% and a PAA binder having a solid content of 3 to 8 wt% are mixed to obtain a negative electrode glue, and the mass ratio of the CMC-Li binder to the PAA binder is 1:(2 to 5); preferably 2:7. Specifically, the solid content of the CMC-Li binder can be 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, etc., or any value within the above range; preferably 1.2%. The solid content of the PAA binder can be 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, etc., or any value within the above range; preferably 6 wt%.

[0038] A CMC-Li binder with a solid content of 1-1.5 wt% can be prepared using water as a solvent. A PAA binder with a solid content of 3-8 wt% can be prepared using water as a solvent.

[0039] In some embodiments, the mass ratio of the CMC-Li binder, the PAA binder, and the SBR binder is preferably 2:7:6.

[0040] In some embodiments, the volume ratio of the primary mixed negative electrode paste, the secondary mixed negative electrode paste, and the tertiary mixed negative electrode paste is (1.5-2.5):1:(1.5-2.5); preferably 2:1:2.

[0041] In the embodiments of the present application, by coordinating the mixing temperature, stirring speed, glue addition order and other conditions, the materials can be mixed more evenly, the pore-forming agent can be evenly dispersed in the slurry, and a stable high bonding force can be formed between the negative electrode particles, which can effectively improve the service life of the negative electrode sheet after it is made into a pole sheet.

[0042] In some embodiments, the total amount of the binder is 2.5-3.5wt% of the total mass of the negative electrode glue, the negative electrode active material, and the conductive agent. Specifically, the total amount of the binder can be 2.5%, 2.8%, 3%, 3.2%, 3.5%, etc., of the total mass of the negative electrode glue, the negative electrode active material, and the conductive agent, or any value within the above range.

[0043] In some embodiments, NH 4 HCO 3 The amount of NH 4 HCO 3 The dosage is 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2% of the sum of the mass of the negative electrode glue, the negative electrode active material, and the conductive agent, or any value within the above range.

[0044] Furthermore, the total amount of binder and NH 4 HCO 3 The dosage ratio is (2.5~4):1. Specifically, the total amount of binder and NH 4 HCO 3 The usage ratio is 2.5:1, 2.8:1, 3:1, 3.2:1, 3.5:1, 3.8:1, 4:1, etc., or any value within the above range.

[0045] In the embodiment of the present application, by optimizing the amount of binder and pore former, the binder can not only better wet the main material, but also increase the bonding force between negative electrode particles and between particles and negative electrode current collector, thereby slowing down particle pulverization or peeling from the current collector, delaying the aging of negative electrode pole pieces, and extending the service life of the battery cell. Moreover, the pore former can be evenly distributed in the negative electrode slurry, so that the pore former can be quickly decomposed during the drying process, forming uniform and structurally equivalent pores on the surface of the pole piece, and improving the dynamic performance of the battery.

[0046] In some embodiments, the negative electrode active material is selected from a composite material of graphite and silicon-carbon, wherein the mass ratio of graphite to silicon-carbon is (90-94):(3-7). Furthermore, the silicon content in the silicon-carbon material is 20-80 wt %, and the carbon content is correspondingly 80-20 wt %.

[0047] In some embodiments, the conductive agent is selected from at least one of conductive carbon black (SP), acetylene black (ACET), Ketjen black, carbon dots (CDs), carbon nanotubes (CNT), graphene (GPE), carbon nanofibers (CNF), and superconducting carbon; preferably conductive carbon black.

[0048] In some embodiments, the negative electrode current collector is selected from copper foil with a conductive carbon black primer, and the thickness of the conductive carbon black primer is 0.5-1 μm.

[0049] In some embodiments, the coating density of the negative electrode slurry on the surface of the negative electrode current collector is 90-120 g / m 2 Specifically, the coating density of the negative electrode slurry on the negative electrode current collector surface is 90g / m 2 , 95g / m 2 , 100g / m 2 , 105g / m 2 , 110g / m 2 , 115g / m 2 , 120g / m 2 etc., or any value within the above range.

[0050] In some embodiments, the thickness of the negative electrode sheet is 50-70 μm. Specifically, the thickness of the thick electrode is 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, etc., or any value within the above range.

[0051] In some embodiments, the mass percentage of deionized water in the negative electrode slurry is 4-10wt%, preferably 5wt%.

[0052] In the negative electrode slurry suitable for the embodiment of the present application, each component includes negative electrode graphite, negative electrode silicon carbon, glue, SBR, NMP, CNT, NH 4 HCO 3 The negative electrode slurry was prepared by mixing in a mass ratio of 91:5:1.8:1.2:0.5:1:1.

[0053] In some embodiments, during the preparation of the negative electrode sheet, the temperature is controlled within the range of 20-35°C.

[0054] The negative electrode plate involved in the embodiment of the present application is prepared by the above method.

[0055] The lithium-ion battery involved in the embodiment of the present application includes the above-mentioned negative electrode plate or the negative electrode plate made by the above-mentioned method.

[0056] Lithium-ion batteries also include electrolyte, separator and positive electrode. The negative electrode, separator and positive electrode can be stacked in sequence to form a battery cell through a winding process or a lamination process. The battery cell is loaded into the aluminum-plastic film that has been punched and formed, and the battery cell is baked. Then, the electrolyte is injected into the baked and dried battery cell so that the battery cell is immersed in the electrolyte. Then, vacuum packaging, standing, formation and other processes are performed to complete the preparation of the lithium-ion battery.

[0057] The electrolyte, the isolation membrane and the positive electrode plate can be made of any known materials, and this application does not limit this.

[0058] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer coated on the surface of the positive electrode current collector. The positive electrode current collector is a conventional metal foil or a composite current collector, such as aluminum foil.

[0059] In some embodiments, the positive electrode material layer is formed by coating the positive electrode slurry on the surface of the positive electrode current collector.

[0060] In some embodiments, the positive electrode slurry includes a positive electrode active material, a conductive agent, and a binder. The positive electrode active material includes but is not limited to lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, ternary LiNixCoyMnzO 2 One or more of the materials (where x+y+z=1, x≥y). The conductive agent includes but is not limited to at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The binder includes but is not limited to at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0061] In some embodiments, the diaphragm described in the present application can be arbitrarily selected from known porous structure diaphragms with good chemical stability and mechanical stability. The material of the diaphragm can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film, without particular limitation. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0062] In some embodiments, the electrolyte described in the present application may be selected from an electrolyte comprising a solvent, an additive and a lithium salt. Among them, the lithium salt may be selected from at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bisfluorooxalate borate, lithium bisoxalate borate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylimide, lithium difluorooxalate phosphate, and lithium perchlorate. The concentration of the lithium salt in the electrolyte is 0.9mol / L to 1.3mol / L. The solvent may be selected from one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, and dimethyl carbonate, and the carboxylic acid ester solvent may be selected from one or more of ethyl propionate, ethyl acetate, and propyl propionate. The additive may be selected from one or more of ethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethyl carbonate, and bisfluoroethylene carbonate. Each component can be freely combined without special restrictions.

[0063] The present application also provides an electrical device or various energy storage systems using batteries as energy storage elements. Electrical devices include but are not limited to mobile phones, tablets, computers, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc.

[0064] In order to make the present invention easier to understand, the present invention will be further described in detail below in conjunction with examples, which are merely illustrative and are not intended to limit the scope of application of the present invention. The raw materials or components used in the present invention can be obtained by commercial routes or conventional methods unless otherwise specified.

[0065] Example 1 (1) Preparation of electrolyte Propylene carbonate (PC), propyl propionate (PP), ethyl propionate (EP), and ethylene carbonate (EC) are mixed in a mass ratio of 1:1:1:1. Based on the total mass of the electrolyte, 12.6% of fluoroethylene carbonate is added. After mixing evenly, LiPF6 is added to obtain an electrolyte with a LiPF6 concentration of 1.1 mol / L.

[0066] (2) Preparation of positive electrode sheet The positive electrode active material is lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ), conductive agent CNT (Carbon Nanotube), binder PVDF (polyvinylidene fluoride), are mixed in a mass ratio of 95:1.5:1.5, and are fully stirred and mixed in N-methylpyrrolidone solvent to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector Al foil, and then the positive electrode sheet is obtained through drying, rolling, compacting and other processes.

[0067] (3) Preparation of negative electrode sheet I. Preparation of negative electrode glue a. Using water as solvent, prepare CMC-Li binder with a solid content of 1.2% and PAA binder with a solid content of 6%.

[0068] b. A mixed adhesive solution was prepared by mixing a CMC-Li binder with a solid content of 1.2% and a PAA binder with a solid content of 6% in a mass ratio of 2:7, with a stirring time of 30 minutes and a vacuum degassing time of 120 minutes.

[0069] II. Negative electrode slurry preparation a. Mix the negative electrode main materials graphite and silicon carbon in a mass ratio of 91:5, stir for 5 minutes, rotate at a speed of 200 rpm, revolve at a speed of 20 rpm, and control the temperature at 32°C.

[0070] b. Add 2 / 5 of the glue, CNT and 1 / 5 of the water into the stirring tank based on step (a). Stir for 100 min, with a rotation speed of 200 rpm, a revolution speed of 20 rpm, a temperature of 32°C, and scrape the stirring paddle.

[0071] c. Add 1 / 5 of the glue solution on the basis of step (b), stir for 80 min, rotate at 1800 rpm, orbit at 20 rpm, and control the temperature at 32°C.

[0072] d. Add the remaining 2 / 5 glue, 4 / 5 water, NMP, NH 4 HCO 3 , stirring time 80min, rotation speed 2000rpm, revolution speed 20rpm, temperature controlled at 32℃, and viscosity tested after stirring.

[0073] e. Add SBR binder on the basis of step (d), and adjust the viscosity by adding water according to the measured viscosity to obtain a negative electrode slurry with a discharge viscosity within the range of 6500 Pa·s.

[0074] Among them, negative electrode graphite, negative electrode silicon carbon, glue, SBR, NMP, CNT, NH 4 HCO 3 Deionized water was added in a mass ratio of 91:5:1.8:1.2:0.5:1:1, accounting for 5% of the mass ratio of the negative electrode slurry.

[0075] III. Preparation of negative electrode The negative electrode slurry obtained in step (2) was coated on a 0.5 μm thick SP-coated copper foil to form a surface density of 90 g / m 2 The negative electrode sheet is dried in an oven at 100°C, rolled and cut to obtain a negative electrode with a thickness of 65 μm. Figure 1 shown.

[0076] (4) Preparation of lithium-ion batteries PE porous polymer film is used as the isolation membrane.

[0077] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrodes to play a role of isolation, and then the stacked electrode sheet and separator are wound to obtain a roll core. The bare roll core is placed in the aluminum-plastic film that has been punched and formed, and the electrolyte prepared above is injected into the baked and dried battery cell. After vacuum packaging, standing, formation and other processes, the preparation of the lithium-ion battery is completed.

[0078] Example 2 The difference from Example 1 is that the discharge viscosity of the negative electrode slurry is 8000 Pa·s.

[0079] Example 3 The difference from Example 1 is that the discharge viscosity of the negative electrode slurry is 9500 Pa·s.

[0080] Example 4 The difference from Example 1 is that the negative electrode graphite, negative electrode silicon carbon, glue, SBR, NMP, CNT, NH 4 HCO 3 Add in a mass ratio of 91:5:1.8:1.2:0.5:1:10.

[0081] Example 5 The difference from Example 1 is that the negative electrode graphite, negative electrode silicon carbon, glue, SBR, NMP, CNT, NH 4 HCO 3 Add in a mass ratio of 91:5:1.8:1.2:0.5:1:0.5.

[0082] Example 6 The difference from Example 1 is that the negative electrode graphite, negative electrode silicon carbon, glue, SBR, NMP, CNT, NH 4 HCO 3 Add in a mass ratio of 92:5:0.8:0.2:0.5:2:1.

[0083] Comparative Example 1 The difference from Example 1 is that NH 4 HCO 3 .

[0084] Comparative Example 2 The difference from Example 1 is that the discharge viscosity of the negative electrode slurry is 6000 Pa·s.

[0085] Comparative Example 3 The difference from Example 1 is that the discharge viscosity of the negative electrode slurry is 10000 Pa·s.

[0086] Comparative Example 4 The difference from Example 1 is that it includes the following steps: CMC-Li binder, PAA binder, SBR binder, graphite, silicon carbon, CNT, NMP, NH 4 HCO 3 and deionized water in proportion to prepare a negative electrode slurry with a discharge viscosity of 6500 Pa·s; The negative electrode slurry is coated on the surface of the negative electrode current collector, dried at 100° C., and roll-pressed to obtain a thick electrode.

[0087] Lithium-ion battery performance test: 25℃ Cycle Test In a (25±2)℃ constant temperature box, the lithium-ion battery is charged to 4.45V at 1C constant current and constant voltage, the cut-off current is 0.05C, and then discharged to 3V at 1C. Multiple charge and discharge cycles are performed under the above conditions. The capacity retention rate of the battery after 800 cycles is calculated. The average capacity retention rate of each group of 5 batteries after 25℃ cycling is recorded in Table 1.

[0088] Capacity retention rate (%) = discharge capacity at the 800th cycle (mAh) / discharge capacity at the third cycle (mAh) × 100% (2) 25℃ storage test In a (25±2)℃ constant temperature box, charge the lithium-ion battery to 4.5V at 1C constant current and constant voltage, with a cut-off current of 0.05C. Test the cell thickness H 1 ; Then place the battery cell in a constant temperature box at (25±2)℃ for 36 hours, take out the battery cell from the high temperature oven and test the thickness of H 2 There are 5 batteries in each group. The thickness expansion rate is calculated and the average value is recorded in Table 1.

[0089] High temperature storage thickness expansion rate (%) = (H 2 -H 1 ) / H 1 *100% Table 1

[0090] The data of Example 1 and Comparative Example 1 show that the addition of pore-forming agent NH 4 HCO 3 , the gas generated by its decomposition after being heated can form pores on the negative electrode sheet, thereby forming a porous negative electrode sheet, which is conducive to the contact between the electrolyte and the electrode sheet, and promotes the embedding of lithium ions in the negative electrode in the pores. Compared with the electrode sheet without through holes, it can greatly reduce the tortuosity of the electrode sheet, shorten the migration distance of lithium ions, and improve the dynamic performance of the battery. At the same time, it can alleviate the volume expansion and contraction of the silicon negative electrode during the charging and discharging process, and delay the aging of the electrode sheet. At the same time, after the electrolyte enters the pores, it will form a solid SEI film on the surface of the negative electrode particles at the pores during the formation stage. The formation of the SEI film at the pores will prevent the further reaction of the electrolyte and the negative electrode active material, so as to improve the cycle performance and service life of the battery cell.

[0091] The data of Examples 1-3, Comparative Example 2 and Comparative Example 3 show that the viscosity of the negative electrode slurry is related to the pore-forming agent NH 4 HCO 3The pore-forming effect on the electrode is closely related. If the discharge viscosity of the negative electrode slurry is too low, the pore-forming agent may precipitate or aggregate in the slurry, resulting in uneven distribution, and will cause the negative electrode active material layer to collapse easily, and pores cannot be effectively formed, or the formed pores are too small to meet the needs of electrolyte and lithium ion transmission, and the capacity retention rate cannot be maintained. In addition, the ability to alleviate the volume expansion and contraction of the silicon negative electrode is poor, which will affect the service life of the battery cell. When the discharge viscosity of the negative electrode slurry is too high, it will hinder the drying and compaction process of the electrode, and the pore-forming agent cannot be evenly dispersed, and uneven distribution will also occur. The pore structure formed will be irregular, resulting in uneven local electrolyte distribution, affecting the embedding and de-embedding process of lithium ions in the electrode, and reducing the charge and discharge efficiency and cycle life of the battery.

[0092] Therefore, the discharge viscosity of the negative electrode slurry is limited to 6500~9500 Pa·s, which is conducive to the formation of porous negative electrode sheets, can improve the transport rate of lithium ions, slow down the pulverization of negative electrode particles caused by the volume change of silicon negative electrode and the peeling between the negative electrode particles and the current collector, thereby delaying the aging of the battery negative electrode sheet, which is beneficial to improving the cycle performance and service life of the battery cell.

[0093] The data from Example 1 and Comparative Example 4 show that the method of adding the negative electrode glue in batches is beneficial to better wetting the main material with the glue, increasing the adhesion between the particles of the negative electrode active material, the conductive agent, etc. and between the particles and the negative electrode collector, helping to slow down the pulverization of the negative electrode particles introduced by the silicon-carbon negative electrode due to repeated volume contraction and expansion, as well as the peeling between the negative electrode particles and the negative electrode collector, delaying the aging of the negative electrode sheet of the lithium-ion battery and extending the service life of the battery cell.

[0094] The data of Examples 1, 4 and 5 show that the pore-forming agent NH 4 HCO 3 If the dosage is too high, it will easily settle in the negative electrode slurry and cannot be evenly dispersed on the surface of the negative electrode to form a uniform porous negative electrode, which is not conducive to maintaining the cycle performance of the battery cell and is not conducive to slowing down the aging of the electrode caused by the volume expansion and contraction of the silicon negative electrode. 4 HCO 3 If the dosage is too low, sufficient pores cannot be formed on the surface of the negative electrode plate, which is not conducive to maintaining the cycle performance of the battery cell, and is not conducive to slowing down the aging of the plate caused by the volume expansion and contraction of the silicon negative electrode.

[0095] The data of Example 1 and Example 6 show that if the amount of binder used is too low, it will be difficult to strongly bond the negative electrode particles to each other and between the negative electrode particles and the negative electrode current collector, which is not conducive to slowing down the pulverization of the negative electrode particles and the peeling between the negative electrode particles and the current collector caused by repeated volume shrinkage and expansion of the silicon-carbon negative electrode, accelerating the aging of the battery negative electrode sheet and worsening the service life of the battery cell.

[0096] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present application may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.

Claims

1. A method for preparing a negative electrode sheet for a lithium ion battery, characterized in that: The following steps are involved: 1) Mixing CMC-Li binder and PAA binder to obtain negative electrode glue; 2) the negative electrode glue is mixed evenly with the negative electrode active material, the conductive agent, NMP, NH4HCO3 and deionized water, and then an SBR binder is added to prepare a negative electrode slurry with a discharge viscosity of 6500-9500 Pa·s; 3) coating the negative electrode slurry on the surface of the negative electrode current collector, drying and rolling to obtain a negative electrode sheet; the NH4HCO3 decomposes and generates gas during the drying step, which promotes the formation of a porous structure in the negative electrode sheet.

2. The preparation method according to claim 1, characterized in that: The step 2) comprises: 2a) taking a portion of the negative electrode glue in step 1) as a primary mixed negative electrode glue, mixing the primary mixed negative electrode glue with the negative electrode active material, the conductive agent and deionized water, and stirring for 90 to 120 minutes at a speed of 100 to 300 rpm to obtain a primary conductive glue; 2b) taking a portion of the negative electrode glue in step 1) as a secondary mixed negative electrode glue, adding the secondary mixed negative electrode glue to the primary conductive glue, stirring for 60 to 80 minutes at a speed of 1800 to 2000 rpm to obtain a secondary conductive glue; 2c) taking a portion of the negative electrode glue in step 1) as a tertiary mixed negative electrode glue, adding the tertiary mixed negative electrode glue, deionized water, NMP and NH4HCO3 to the secondary conductive glue, stirring for 60-90 minutes at a speed of 1800-2100 rpm; after mixing evenly, adding SBR binder to prepare a negative electrode slurry with an output viscosity of 6500-9500 Pa·s.

3. The preparation method according to claim 2, characterized in that: The volume ratio of the primary mixed negative electrode glue, the secondary mixed negative electrode glue and the tertiary mixed negative electrode glue is (1.5-2.5):1:(1.5-2.5).

4. The preparation method according to claim 1, characterized in that: The total amount of the binder is 2.5-3.5wt% of the sum of the mass of the negative electrode glue, the negative electrode active material and the conductive agent; The amount of NH4HCO3 used is 0.6-1.2wt% of the sum of the mass of the negative electrode glue, the negative electrode active material and the conductive agent.

5. The preparation method according to claim 4, characterized in that: The ratio of the total amount of the binder to the amount of the NH4HCO3 is (2.5~4):

1.

6. The preparation method according to claim 1, characterized in that: The negative electrode active material is selected from a composite material of graphite and silicon carbon, and the mass ratio of the graphite to the silicon carbon is (90-94):(3-7); And / or, the conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers, and superconducting carbon.

7. The preparation method according to claim 1, characterized in that: The negative electrode current collector is selected from copper foil with a conductive carbon black primer, and the thickness of the conductive carbon black primer is 0.5-1 μm.

8. The preparation method according to claim 1, characterized in that: In the step 1), a CMC-Li binder with a solid content of 1-1.5 wt% and a PAA binder with a solid content of 3-8 wt% are mixed to obtain a negative electrode glue, and the mass ratio of the CMC-Li binder to the PAA binder is 1:(2-5).

9. The preparation method according to claim 1, characterized in that: The drying temperature in step 3) is 95-110°C.

10. The preparation method according to any one of claims 1 to 9, characterized in that: The thickness of the negative electrode active material layer on the negative electrode plate is 50-70 μm.

11. A lithium-ion battery, comprising a negative electrode sheet prepared by the preparation method according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Lithium ion battery negative electrode plate and preparation method thereof, and lithium ion battery

    CN107919459A

  • Negative electrode material binder for low-temperature lithium ion battery, negative electrode material, negative electrode plate and preparation method

    CN115360350A

  • Lithium ion battery negative electrode and preparation method thereof

    CN115548343A

  • Porous negative pole piece, preparation method thereof and lithium ion battery

    CN115632105A

  • Preparation method of porous negative pole piece of lithium ion battery

    CN116759542A